2013
DOI: 10.1097/pas.0b013e31828a6727
|View full text |Cite
|
Sign up to set email alerts
|

Clear Cell Odontogenic Carcinomas Show EWSR1 Rearrangements

Abstract: Clear cell odontogenic carcinomas (CCOCs) are a rare tumor of the jaws, which have considerable morphologic and immunophenotypic overlap with (hyalinizing) clear cell carcinomas (CCCs) of salivary origin. Fluorescence in situ hybridization for EWSR1 was performed on 12 CCOCs, 14 CCCs, and a control set of other miscellaneous clear cell tumors of the head and neck region. EWSR1 was rearranged in 12/13 (92.3%) CCCs and 5/8 (62.5%) CCOCs. EWSR1 testing failed in 1 CCC and 4 CCOCs. Two cases initially diagnosed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 166 publications
(38 citation statements)
references
References 9 publications
4
34
0
Order By: Relevance
“…PTCH1 mutations are reported in odontogenic keratocysts with or without association to nevoid basal cell carcinoma syndrome (Qu et al, 2015;Wright, Odell, Speight, & Takata, 2014). In malignant tumors, BRAFV600E has been observed in ameloblastic carcinoma and clear cell odontogenic carcinoma (Diniz et al, 2015), as well as the fusion gene EWSR1-ATF1 has been reported in clear cell odontogenic carcinoma (Bilodeau et al, 2013). In this study, we used immunohistochemistry to localize BRAFV600E in the AOT tissues but no case was positive confirming that this mutation is not present in AOT (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…PTCH1 mutations are reported in odontogenic keratocysts with or without association to nevoid basal cell carcinoma syndrome (Qu et al, 2015;Wright, Odell, Speight, & Takata, 2014). In malignant tumors, BRAFV600E has been observed in ameloblastic carcinoma and clear cell odontogenic carcinoma (Diniz et al, 2015), as well as the fusion gene EWSR1-ATF1 has been reported in clear cell odontogenic carcinoma (Bilodeau et al, 2013). In this study, we used immunohistochemistry to localize BRAFV600E in the AOT tissues but no case was positive confirming that this mutation is not present in AOT (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…29, 30, 31, 32, 33 EWSR1 gene rearrangement also can be seen in extraskeletal myxoid chondrosarcoma, clear cell sarcoma, hyalinizing clear cell carcinoma, clear cell odontogenic carcinoma, desmoplastic small round cell tumor, and myxoid liposarcoma. 34, 35, 36, 37, 38, 39 Thus, corroborating morphologic, immunophenotypic, and genetic features is required for a definitive ES diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Available clinical and demographic parameters were obtained. Cases not included for review in this study were: 6 cases of ''carcinomas ex Schneiderian papillomas (reported from our institution previously)'' [20], and 2 ''clear cell/sinonasal renal cell like adenocarcinoma (one also reported previously by us)'' [21].…”
Section: Case Selectionmentioning
confidence: 99%